8(x-1)+9=5x+3(-1+x)

Simple and best practice solution for 8(x-1)+9=5x+3(-1+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x-1)+9=5x+3(-1+x) equation:


Simplifying
8(x + -1) + 9 = 5x + 3(-1 + x)

Reorder the terms:
8(-1 + x) + 9 = 5x + 3(-1 + x)
(-1 * 8 + x * 8) + 9 = 5x + 3(-1 + x)
(-8 + 8x) + 9 = 5x + 3(-1 + x)

Reorder the terms:
-8 + 9 + 8x = 5x + 3(-1 + x)

Combine like terms: -8 + 9 = 1
1 + 8x = 5x + 3(-1 + x)
1 + 8x = 5x + (-1 * 3 + x * 3)
1 + 8x = 5x + (-3 + 3x)

Reorder the terms:
1 + 8x = -3 + 5x + 3x

Combine like terms: 5x + 3x = 8x
1 + 8x = -3 + 8x

Add '-8x' to each side of the equation.
1 + 8x + -8x = -3 + 8x + -8x

Combine like terms: 8x + -8x = 0
1 + 0 = -3 + 8x + -8x
1 = -3 + 8x + -8x

Combine like terms: 8x + -8x = 0
1 = -3 + 0
1 = -3

Solving
1 = -3

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 9x-11y=99 | | 14x^2+19=47 | | d^2-8d+144=145 | | 10x-6=9x+1 | | Y=.23x+.55 | | 343x^3= | | X^4-x^2=400 | | 3(4p+1)-2(p-5)= | | Y=.23+.55 | | X+.75x=140 | | x^2+169x+26=19 | | 4x^4+5x^2=8 | | x^2-10x-25=14 | | 8+3x-x=6 | | 21=w^2+4w | | 30=-x+100 | | (-3x-7)+(4x+7)=0 | | Tanx*cotx= | | 3x^2-4x+150=0 | | 2x*3x=10*(10x+10) | | 1/3x-15/120x= | | 0=2x^2+11x+21 | | -7(7x-3)+1=-49x+22 | | 22x-45=93 | | 0.75(2x-5)=0.50(x+2) | | 2x-4=3(x+6) | | X(x+3x)=8(8+(x+2)) | | 64-x=73-2x | | log[4]2*x=0 | | a(7x+3)=b-21x | | y-4=30 | | 7*49=x*8x |

Equations solver categories